Stratification features of the Pontian sediments in the Southern Ukraine by means of ostracods - Kovalenko, V.A.; Vernihorova, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The study generalizes the species composition data, paleoecological characteristics, and patterns of the vertical distribution of ostracod complexes in the Pontian regiostage sediments of the Southern Ukraine.